Identidades femininas múltiplas em crônicas de Clarice Lispector - Pajolla, Alessandra Dalva de Souza (2010)
This dissertation examines the multiple female identities in chronics written by Clarice Lispector for the Jornal of Brazil, between 1967 and 1973, subsequently published in The discovery of the world (1984). If in the novels and stories she subverted the patriarchal ideology and was a landmark in the literature written by women in Brazil, in the chronicles Clarice Lispector increased representation of women. Rejecting the essentialist perspective, the writer represented various characters, women who couldn?t been represented by a single category. The middle-class woman shares with maids, prostitutes and missionaries. Here is the focus of this study: the different female voices in chronics, hybrid territory between journalism and literature, fiction and reality. Understanding the process of forming their own identity, undertaken by the women represented in the chronicles, is the main objective of the research. The Feminist Critical Theory opened the horizon of questions about the hierarchical division between the genders, prejudice, stereotyping and marginalization of female writing. The research included discussions that marked the feminist thought and its new approaches to studies on the subject of displacement and fragmentation of identity in the late modernity, showing ways to understand, in a non-essentialist perspective, the characters of chronics by Clarice Lispector.